Staphylinid diversity (Coleoptera: Staphylinidae) in five productive systems in the Colombian Andes - SANABRIA-B., CATALINA; ARMBRECHT, INGE; GUTIÉRREZ-CHACÓN, CATALINA (Revista Colombiana de Entomología, 2008)
An adequate agroecological management of ranching systems benefits from the associated entomafauna. The aim of this research was to determine the species of staphylinids in five production systems established along a gradient of plant recovery in the Colombian Andes. The hypothesis was that the diversity was positively associated with the recovery of the arboreal component. The survey was made over two rainy and one dry seasons between 2004 and 2006. Using pitfall traps, 272 beetles were collected, which belonged to five subfamilies and 45 morphospecies. The subfamilies Aleocharinae and Staphylininae were the most diverse, while Anotylus (Oxytelinae) was the most abundant. Pastures with trees exhibited high species richness, which was comparable to that of natural ecosystems such as forests and “guadua” (bamboo-like) forests. Homogeneous vegetation was highly related to a low diversity of staphylinids, and so the components of production ranching systems influence diversity. The different elements of the landscape, however, contribute as a whole to the regional diversity of staphylinids.